Surgical repair of inferior sinus venosus defects: a novel approach with unsnared inferior vena cava. Issue 1 (December 2015) - Lin, Fushun; Tang, Hong; Xiao, Xijun
Abstract Background Inferior sinus venosus defects (SVD) are very rare and difficult to image from transthoracic echocardiography. Surgical errors were occasionally reported in the repair of inferior SVDs. Results The authors have operated on 12 inferior SVD patients using bicaval cannulation with unsnared inferior vena cava (IVC) and proved successful. Conclusion This technique guaranteed a better exposure of surgical field and facilitate identifying the anatomical relationship between lower part of the SVD and IVC orifice, thus avoiding postoperative IVC - left atrial shunt and other surgical mistakes.